Canva-assisted Modelling the Way strategy and students' Islamic education learning outcomes - Sunarso, Ali; Herdianto, Fiky (LPMPP Universitas Negeri Yogyakarta, 2024)
The teacher's lecture and question-and-answer method do not provide meaningful engagement for students, necessitating the adoption of different learning strategies. This study aims to determine the effect of the Modelling the Way strategy, assisted by Canva media, on 4th-grade students' Islamic education learning outcomes. This research employed a quantitative approach with a Pre-Experimental Design (non-design) in the form of a One-Group Pretest-Posttest Design. The population in this study consisted of fourth-grade students at SDN 2 Gulang Mejobo Kudus, with a total sample of 31 students. Data collection techniques included observation, interviews, and tests. The results of the t-test show that t_count = 5.380 > t_table = 2.042, so Ha is accepted. The results indicate an effect of the Modelling the Way strategy on the fourth-grade students' Islamic education learning outcomes. The average pretest score was 63.71, and the average posttest score was 79.03. Therefore, there is a significant increase in posttest learning outcomes using the Modelling the Way strategy compared to the pretest.